Red Junglefowl Chicks Seek Contact With Humans During Foraging Task - Rubene, Diana; Løvlie, Hanne (Frontiers in Psychology, 2021)
Contact seeking with humans is documented in some domestic animals, mainly dogs, which have advanced communication skills. Domestication as a companion animal is thought to underlie this ability. However, also domesticated horses and goats display similar human-directed behaviors. This suggests either a broader effect of domestication on contact-seeking behavior, or alternatively, that social interactions with humans can result in the development of human contact seeking. As part of another study, we observed contact-seeking behavior in juvenile red junglefowl (Gallus gallus) chicks exposed to behavioral training since hatching, during a foraging task, where chicks were singly required to collect food rewards in a familiar arena using odor cues. If chicks left the arena, we recorded if they approached and looked up at the experimenter, or if they approached other objects (including another human). Chicks approached the experimenter significantly more often than they approached other objects. This behavior was not linked to a fast performance in the test arena, which gave some birds more time to explore the surroundings, or to learning ability measured in a cognitive task. Yet, the preference for the experimenter was lower for chicks that were handled more prior to the experiment. Also, approach probability was positively correlated with escape attempts in a novel arena test. The observed variation in approach behavior suggests a link to aspects of personality, and exposure to human interactions and experimental procedures. Our observations suggest that, although neither domesticated nor selectively bred, red junglefowl that are socialized with humans can potentially develop behavior used to describe contact seeking. Together with evidence from cognitive and behavioral studies, our results suggest that social experiences, not only domestication, can affect human-animal interactions. We propose how interactions between behavior, cognition and handling could be studied further in controlled settings to validate the preliminary findings of our study and uncover the underlying mechanisms.